Types of deixis in the song lyrics of ariana grande’s thank u, next album - Dewi, Ni Made Savitri; Resen, I Wayan; Santika, I Dewa Ayu Devi Maharani (Journal of Language and Applied Linguistics, 2022)
This research entitled “Type of Deixis in The Song Lyrics of Ariana Grande’s thank u, next Album”. Deixis is an expression in language that in used to point who to person deixis, where to place deixis, and when to time deixis. The objectives in this research is to find out and identify types of deixis in the song lyrics of Ariana Grande’s thank u, next Album. Documentation method is used in collecting the data using listening, reading and note taking techniques. Qualitative method is used to analyze the data by using descriptive language for explaining the data. The result of this research shows that all types of deixis are found in the song lyrics of Ariana Grande’s thank u, next album which include person deixis, spatial deixis, temporal deixis, social deixis and discourse deixis. This research found the occurrences of 550 person deixis (81%), 109 temporal deixis (9%), 7 discourse deixis (1%), 32 spatial deixis (7%), and 19 social deixis (9%).